A Study to Assess the Effectiveness of Awareness Programme on Knowledge Regarding Health Problems Related to Smart Phone Addiction Among Adolescents Studying in a Selected School, Bangalore, Karnataka - Kavita Reddy; Sijo Koshy (International Journal of Evidence Based Nursing And Practices, 2023)
Aim: This study assesses the effectiveness of an awareness program on adolescents' knowledge of health problems related to smartphone addiction. Objectives: (1) Evaluate adolescents' understanding of health issues linked to smartphone addiction. (2) Measure the impact of the awareness program on their knowledge by comparing pre-test and post-test scores. (3) Investigate correlations between pre-test knowledge and sociodemographic variables. Method: A quantitative evaluative approach was used. The one-group pre-test post-test research design involved 60 adolescents (aged 13–16) from a school in Bangalore. Non-probability convenient sampling was employed, and data was collected via a structured questionnaire. Analysis was conducted using Excel. Results: Most participants (50%) were aged 15–16 years, and the majority (60%) of them were female. Half (50%) were in the 10th grade, and 80% belonged to nuclear families. About 60% of fathers had completed graduation, while 40% of mothers had finished secondary education. Most fathers (60%) were non-government employees, and the same percentage of mothers were non-government employees. Half (50%) of the subjects had a family income exceeding 30,000 rupees/month. Over half (67%) spent less than 2 hours daily on smartphones. A majority (85%) did not own smartphones, and 60% received information from family and friends. In the pre-test, 70% had average knowledge, while 30% had poor knowledge, and none had good knowledge. In the post-test, 73% had good knowledge, 27% had average knowledge, and none had poor knowledge. The pre-test knowledge score was 12.93, while the mean post-test knowledge score was 21.7. The 't' value (17.97) was higher than the table value at the 0.05 level of significance. The average knowledge score increased by 8.77 points. Conclusion: The awareness program significantly improved students' understanding of health issues related to smartphone addiction, indicating that it was effective and feasible.
Keywords: Awareness programme; smart phone; smart phone addiction